Formation of Stakeholder Trust in Business and the Role of Personal Values - Pirson, Michael (Journal of business ethics, 2017)
Declining levels of stakeholder trust in business are of concern to business executives and scholars for legitimacy- and performance-related effects. Research in the area of stakeholder trust in business is nascent; therefore, the trust formation process has been rarely examined at the stakeholder level. Furthermore, the role of personal values as one significant influence in trust formation has been under-researched. In this paper, we develop a contingency model for stakeholder trust formation based on the effects of stakeholder-specific vulnerability and personal values of the trustor. Using a factorial vignette methodology, we find that Schwartz’s (J Soc Issues 50:19–45, 1994) value set interacts with stakeholder roles so that trustworthiness signals of competence and character play differing roles during trust formation. These results inform stakeholder trust research, organizational trust research, and research in personal values. The research also informs managers tasked with rebuilding stakeholder trust in business.